KEANEKARAGAMAN VEGETASI TAMAN KOTA SEBAGAI RUANG TERBUKA HIJAU (RTH) DI TAMAN RUM BALIBUNGA KOTA TIDORE KEPULAUAN - Asiah Salatalohy; Abdul Kadir Kamaluddin; Nuriska Nyong (JURNAL HUTAN PULAU-PULAU KECIL, 2023)
The existence of Green Open Space (RTH) is an important element in forming a comfortable and healthy urban environment. The existence of RTH functions, among others, as the lungs of the city, the beauty of the city, and a center for physical health and natural recreation. This study aims to determine the diversity of vegetation types in Rum Balibunga City Park, Tidore Islands City. The method used in this research is a quantitative method to collect data on the types of vegetation found in urban parks using the Shanon Wiener equation. There are 10 types of tree species in the Rum Balibunga park with a total of 101 trees (H'=1.8198, belonging to the medium category), which are dominated by Samanea saman plants. While there are 5 types of ornamental plants with a total of 206 (H' = 1.389 medium category) which are dominated by Aglonema plants.